Modified Aortic Uncrossing Procedure: A Novel Approach for Norwood Palliation of Complex Univentricular Congenital Heart Disease With a Circumflex Aorta. (July 2017) - Bryant, Roosevelt; Wallen, William; Rizwan, Raheel; Morales, David L.
The circumflex aorta is a rare type of true vascular ring anomaly. It consists of a retroesophageal right aortic arch, a left-sided descending thoracic aorta, and a left-sided ligamentum arteriosum. The "aortic uncrossing procedure" described by Planché and Lacour-Gayet is the procedure of choice for managing this aortic anomaly in patients with a biventricular heart. The presence of a circumflex aorta in a patient with heterotaxy syndrome and univentricular congenital heart disease requiring Norwood palliation is highly unusual. We report such a case and describe our approach to its surgical management.